American Economic Journal: Macroeconomics - American Economic Association (Pittsburgh, PA American Economic Association, 2011)
American Economic Journal: Macroeconomics focuses on studies of aggregate fluctuations and growth, and the role of policy in that context. Such studies often borrow from and interact with research in other fields, such as monetary theory, industrial organization, finance, labor economics, political economy, public finance, international economics, and development economics.
American Economic Journal: Macroeconomics is Published quarterly in January, April, July and October.
Keywords: Economics; MACROECONOMICS; ECONOMIC GROWTH; ECONOMIC FLUCTUATIONS